1970
DOI: 10.2337/diab.19.4.234
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Zinc and Copper in Diabetes Mellitus

Abstract: A review of the literature indicated some disagreement concerning plasma zinc levels in diabetes mellitus. Diabetics of both sexes with all degrees of severity of the disease have been studied and compared with controls matched for age and sex. Plasma zinc estimations were performed using a simple dilution method and atomic absorption spectrophotometry. Copper analyses were also carried out by a similar procedure. The results show that there are no significant differences in the nonfasting plasma zinc and copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

1978
1978
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…Serum levels reported in the literature have ranged from normal [11,12] to higher than normal [13] , whereas copper levels observed in the body were altered; for instance, levels in the muscles are lower than in controls in all cases. The disagreement in the values recorded here may be ascribable to differences in the intake of this element, to higher excretion rates, or to differing prevalence rates for the various metabolic complications.…”
Section: Discussionmentioning
confidence: 96%
“…Serum levels reported in the literature have ranged from normal [11,12] to higher than normal [13] , whereas copper levels observed in the body were altered; for instance, levels in the muscles are lower than in controls in all cases. The disagreement in the values recorded here may be ascribable to differences in the intake of this element, to higher excretion rates, or to differing prevalence rates for the various metabolic complications.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies found that in diabetic patients, circulating copper concentrations were not different (21) or were greater in patients with chronic complications or macrovascular diseases (4). Indeed, in the presence of overt diabetes with chronic complications, the associated chronic low-grade inflammatory state might be responsible for an increase in blood copper concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…bei Alkoholikern [20,56], Leberzirrhosen [41,56,63,64], renalen Erkrankungen [62], Sichelzellenan/imie [42], Verbrennungen [10,21], Infektionskrankheiten [1] oder anderen Typen von Entzfindungen und Verletzungen [11,29] beobachtet werden konnte. Einige Patienten mit Diabetes mellitus zeigten ebenfalls eine erh6hte renale Ausscheidung von Zink [37,58], wobei der Plasma-Zn-Gehalt aber unverfindert blieb [36]. Auch die erh6hte Ausscheidung yon Sulfat oder Harnstoff erfolgt erst im weit fortgeschrittenen Stadium des Zn-Mangels und ist daher ftir die Erfassung eines marginalen Zn-Status nicht geeignet [13].…”
Section: Bei Den Jungenunclassified